Sports Marketing for a Greener Indonesia: Challenges and Opportunities in Building a Sustainable Sports Industry - Louk, Michael Johannes Hadiwijaya; Runesi, Salmon; Huwae, Joppi; Shareef, Qays Banwan; Moniz, Pascoela De Jesus (Universitas Negeri Surabaya, 2026)
Purpose: This study examines the integration of sport marketing and sustainability within Indonesia’s growing sports industry, employing a comprehensive mixed-methods approach to identify key challenges, opportunities, and practical strategies for implementing sustainable practices. Materials and Methods: The research employed a mixed-methods design, combining qualitative interviews with 30 industry stakeholders and quantitative surveys of 120 participants. The sample represented diverse sectors, including sports organizations, marketing professionals, athletes, event planners, policymakers, and fans. Result: Findings reveal a significant disconnect between sustainability awareness and practical application; while 65% of respondents demonstrated general awareness of sustainability concepts, only 30% understood their specific relevance to sport marketing. Current initiatives, such as eco-friendly merchandise and green events (25%), were found to be largely ad hoc rather than strategically implemented. Three primary opportunity areas were identified: leveraging Indonesia’s high digital penetration, forming strategic partnerships with sustainability-focused brands, and developing targeted fan engagement campaigns. Notably, 70% of stakeholders recognized the brand reputation benefits of sustainable marketing, though 50% expressed concerns regarding implementation costs and complexity. Conclusion: These findings highlight the critical need for structured educational initiatives and policy support to bridge the awareness-implementation gap. Consequently, the research team developed the